2019
DOI: 10.1002/mus.26653
|View full text |Cite
|
Sign up to set email alerts
|

Viral vector delivery of follistatin enhances recovery of reinnervated muscle

Abstract: Introduction Poor recovery following nerve repair is due to progressive temporal loss of muscle function. Follistatin (FS), a glycoprotein with anabolic properties, may enhance muscle recovery following reinnervation. Methods Seventy‐two male Sprague–Dawley rats underwent temporary (3 or 6 month) denervation or sham denervation. After reinnervation, rats were administered adeno‐associated viral vectors expressing FS deoxyribonucleic acid (isoform FS‐317) injected into the target muscle or sham treatment. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…Likewise, our prior investigation demonstrated that recombinant FST DNA also enhances satellite cell counts after denervation and repair. 25 In the current investigation, there did seem to be a correlation with satellite cell counts and force generation. In groups in which the satellite cell counts were diminished, (3-month sham denervation) force output was reduced and conversely in groups with bolstered satellite cell counts (6-month denervation) force output was enhanced.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…Likewise, our prior investigation demonstrated that recombinant FST DNA also enhances satellite cell counts after denervation and repair. 25 In the current investigation, there did seem to be a correlation with satellite cell counts and force generation. In groups in which the satellite cell counts were diminished, (3-month sham denervation) force output was reduced and conversely in groups with bolstered satellite cell counts (6-month denervation) force output was enhanced.…”
Section: Discussioncontrasting
confidence: 39%
“… 29 We previously demonstrated improved muscle mass, increased type IIB muscle fiber size, and increased satellite cell counts in an identical study with the administration of FST DNA via viral vectors. 25 In contrast to transgenetic manipulation, however, the therapeutic potential of direct FST protein administration has received scant attention. Injecting spinal muscular atrophy mice with recombinant FST increased muscle mass, coordination, and life span.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations